Analysis of Runner Dynamics of Reversible Hydraulic Turbine by Alternating Fluid–Solid Action - Xin, Lu; Li, Qifei; Li, Zhenggui; Xie, Gengda; Wang, Qifan (Frontiers in Energy Research, 2022)
In order to study the dynamic characteristics of water pump turbine runner based on two-way fluid structure coupling, taking a pump turbine model as the research object, the two-way fluid structure coupling method is used to iteratively calculate and analyze the fluid and structural equation, and the influence of water body in the unit channel on the runner under typical working conditions is obtained. The results show that the vortex mainly appears in the back area of the runner blade, and the flow extends from the blade free area to the blade outlet. There is strong pressure pulsation at the inlet. Under different working conditions, the stress region of the runner is obvious, which is concentrated at the connection between the inlet edge of the runner blade and the upper crown and lower ring. The maximum deformation region appears in the lower middle of the blade inlet. Modal analysis shows that the possibility of runner resonance caused by dynamic stress frequency caused by dynamic and static interference is very small.